Hubungan Pengetahuan Gaya Hidup Sehat Dengan Kejadian Obesitas Pada Ibu Rumah Tangga Di Kecamatan Dayeuhluhur - Kintan Permata Hidayat; Idawati Karjadidjaja (CV. Multi Kreasi Media, 2022)
The prevalence of obesity is increasing and is also a risk factor for non-communicable diseases, namely cardiovascular disease, cancer, and diabetes mellitus. Knowing the various factors that can cause obesity is important, one of which is knowledge about a healthy lifestyle. This study aims to assess whether there is a relationship between the level of knowledge of a healthy lifestyle with the incidence of obesity in housewives. The study is an observational analytic study with a cross-sectional method with the research subjects being housewives aged 20-40 years in Dayeuhluhur District. Knowledge measurement was carried out using a questionnaire containing 20 questions. Obesity is determined by measuring body mass index (BMI) and waist circumference. Knowledge categories are divided into good & poor. There are 54 (46,6%) people with less knowledge, 62 (53,4%) people with good knowledge. There were 2 (1,7%) people with underweight nutritional status, 40 (34,5%) people with normal nutritional status, and 74 (63,8%) people with overweight + obesity nutritional status. There were 24 (20,7%) people with normal waist circumference, and 92 (79,3%) people with central obesity. It was concluded that there were relationship between healthy lifestyle knowledge and obesity, which is reflected by the difference of BMI (p-value = 0.000).